2018
DOI: 10.1126/scitranslmed.aau7137
|View full text |Cite
|
Sign up to set email alerts
|

Wnt1 is an Lrp5-independent bone-anabolic Wnt ligand

Abstract: WNT1mutations in humans are associated with a new form of osteogenesis imperfecta and with early-onset osteoporosis, suggesting a key role of WNT1 in bone mass regulation. However, the general mode of action and the therapeutic potential of Wnt1 in clinically relevant situations such as aging remain to be established. Here, we report the high prevalence of heterozygousWNT1mutations in patients with early-onset osteoporosis. We show that inactivation of Wnt1 in osteoblasts causes severe osteoporosis and spontan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
60
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 58 publications
(73 reference statements)
5
60
0
2
Order By: Relevance
“…Together with the reduced osteogenic differentiation of ST2 cells transfected with a mutant Wnt1 expression plasmid, these findings clearly demonstrate the pathogenicity of the WNT1 ‐R235W mutation. Consistent with previously published data showing that Wnt1 deletion or overexpression in osteoblast lineage cells primarily affects bone formation,(23–25) we found that 12‐week‐old Wnt1 R235W/R235W mice displayed a reduced trabecular bone formation rate, which was assessed in spine sections. Of note, this difference was observed before a significant reduction of the trabecular bone volume was identified in the respective vertebral bodies.…”
Section: Discussionsupporting
confidence: 92%
“…Together with the reduced osteogenic differentiation of ST2 cells transfected with a mutant Wnt1 expression plasmid, these findings clearly demonstrate the pathogenicity of the WNT1 ‐R235W mutation. Consistent with previously published data showing that Wnt1 deletion or overexpression in osteoblast lineage cells primarily affects bone formation,(23–25) we found that 12‐week‐old Wnt1 R235W/R235W mice displayed a reduced trabecular bone formation rate, which was assessed in spine sections. Of note, this difference was observed before a significant reduction of the trabecular bone volume was identified in the respective vertebral bodies.…”
Section: Discussionsupporting
confidence: 92%
“…This pathway has been shown to contribute to cervical cancer pathology in various stages, including tumor initiation, progression, invasion, and therapeutic resistance [39,40]. As a member of the Wnt family, Wnt1 has been shown to involve in tumor progression, adaptive immune resistance and bone remodeling [41][42][43]. In our study, we identified Wnt1 as a key downstream effector of NEK2 in cervical cancer.…”
Section: Discussionmentioning
confidence: 61%
“…Loss of Wnt5a specifically in osteoclasts leads to reduced bone mass due to decreased bone formation, whereas deletion of its receptor Ror2 in OCs leads to increased bone mass, suggesting that Wnt5a activates both osteoblasts and osteoclasts, with a predominant effect on osteoblast function [22,35]. Mutations in Wnt1 have been shown to be responsible for osteoporosis and osteogenesis imperfecta, and transgenic overexpression of Wnt1 has been shown to markedly increase bone mass in mice [4,36]. In this study we found deregulation of Wnt5a as well as Wnt1 accompanying the increased osteoblast activity in miR-146a deficient mice.…”
Section: Discussionmentioning
confidence: 99%